Description of Education Service Quality in LKP Sanggar Tari Permata Hati Parupuk Tabing - Silfi Nurfitra; Alim Harun Pamungkas (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research was written based on the succcess programe of LKP Sanggar Tari Permata Hati in increasing its existence. It can be seen from it’s free training, training based on the trainees needs,  trusted by society,  increase in number of trainee and the close relation between the trainers and the trainees. The purpose of this research is to show the education service quality of LKP Sanggar Tari Permata Hati according to it’s responsiveness and empathy dimensions. This research is a descritptive quantitaive research. There are 50 people of  population and 25 people of  sample which is gotten by using cluster random sampling technique. The researcher uses questioner as the instrument and percentage formulation for the analysis. This research shows that (1) the education service quality based on responsiveness dimension has applied well, (2) the education service quality based on empathy dimension has applied well. Based on this research, the researcher suggests the admistrators of institute to develope the education service quality for the institution advancement.Keywords: Service Quality, LKP, Course, Education Service